O fazer dos assistentes sociais juntos às famílias nos Centros de Referência de Assistência Social - CRAS do município de São Bernardo do Campo/SP - França, Marina (2010)
In a country whose history is marked by significant social inequalities, the political culture in the social assistance area is strongly linked to a series of actions characterized by depoliticized forms of approach to social issues. As a consequence, in the trajectory of social assistance, charity and philanthropy were and still are, in many instances, significant actors. The current National Social Assistance Policy PNAS, introduces significant changes, committed to the attendance to the needs and rights of the population; we are, on the other hand, going through an historic period in which the advance of neoliberal policies opposes the realization of social policies under the responsibility of the State, which limits the possibility of advances in social attendance policies. Considering the trajectory of social assistance and the impasse mentioned above, the objective of this thesis is to learn and analyze the actions that are being implemented in the professional routine, as refers to attendance to families in the area of basic social protection since the implementation of the Unified Social Assistance System- SUAS. In order to achieve this objective we have chosen São Bernardo do Campo SBC, a municipality in the state of São Paulo where we exercise our activities as court social assistant